2020
DOI: 10.3390/coatings10070650
|View full text |Cite
|
Sign up to set email alerts
|

Study of Sputtered ZnO:Ga2O3 Films for Energy Harvesting Applications

Abstract: Thin films of ZnO:Ga2O3 (ZGO) were deposited by radio frequency (RF) sputtering at voltages of 0.5, 0.9 and 1.1 kV. The films were studied with respect to their suitability in flexible piezoelectric nanogenerators. The analysis of the spectroscopic and microscopic results showed that piezoelectric features were revealed for the films grown at all sputtering voltages, but the most favorable morphology in terms of low roughness was achieved at 1.1 kV. The effect of the sputtering voltage on the films cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Bouhemadou et al concluded that the bulk modulus (B 0 ) and elastic constants (C ij ) are linear positive correlations to the pressure for ZnGa 2 O 4 [50]. Their results may be considered as reliable predictions of the pressure dependence of the elastic properties [50] for the ZnGa 2 O 4 material, excluding low-frequency vibrational harvesting, which could be a pressure sensor or strain gauge, due to the good linearity of the electrical parameter dependences on the strain [22]. The values for the elastic constants were C 11 = 228 GPa, C 12 = 120 GPa, C 44 = 107 GPa, and bulk modulus B 0 =156 GPa when the pressure was subjected to zero.…”
Section: Mechanical Properties Of Znga 2 O 4 Under External Pressurementioning
confidence: 97%
See 2 more Smart Citations
“…Bouhemadou et al concluded that the bulk modulus (B 0 ) and elastic constants (C ij ) are linear positive correlations to the pressure for ZnGa 2 O 4 [50]. Their results may be considered as reliable predictions of the pressure dependence of the elastic properties [50] for the ZnGa 2 O 4 material, excluding low-frequency vibrational harvesting, which could be a pressure sensor or strain gauge, due to the good linearity of the electrical parameter dependences on the strain [22]. The values for the elastic constants were C 11 = 228 GPa, C 12 = 120 GPa, C 44 = 107 GPa, and bulk modulus B 0 =156 GPa when the pressure was subjected to zero.…”
Section: Mechanical Properties Of Znga 2 O 4 Under External Pressurementioning
confidence: 97%
“…excluding low-frequency vibrational harvesting, which could be a pressure sensor or strain gauge, due to the good linearity of the electrical parameter dependences on the strain [22]. The values for the elastic constants were C11 = 228 GPa, C12 = 120 GPa, C44 = 107 GPa, and bulk modulus B0 =156 GPa when the pressure was subjected to zero.…”
Section: Band Structure Of Znga 2 Omentioning
confidence: 99%
See 1 more Smart Citation
“…All piezoelectric samples were fabricated with near to ohmic contacts to avoid a measurement error caused by the interface barriers voltage drop. It was previously established that for piezoelectric films of GZO, the most appropriate electrode material was silver (Ag), for KNbO 3 , aluminum (Al) and for BST:PVDF-TrFE composite, Ag [20,21]. The top electrodes were patterned by lift-off process to produce a variety of similar segments for impedance spectroscopy probing.…”
Section: Methodsmentioning
confidence: 99%
“…RF voltage and post heat treatment temperature have influence on the fabricated 32 film. Aleksandrova et al [184] prepared ZnO/Ga2O3 films at different voltages of 0.5 kV, 0.9 kV and 1.1 kV.…”
Section: Rf Sputteringmentioning
confidence: 99%